Mad housewife and cool girl: Gillian Flynn’s Gone Girl as feminist metafiction - Szarvas, Réka (AMERICANA E-journal of American Studies in Hungary, 2018)
The aim of the paper is to interpret Gillian Flynn’s novel, Gone Girl (2012) as a feminist metafictional narrative. The novel belongs to the genre of crime fiction, but it also provides a self-reflective critique on ideologically engendered writerly modes and cultural scripts associated with women. The first half of the paper offers a summary of the theoretical background to the analysis: an overview on metafiction and feminist metafiction that serve as a contextual framework for the succeeding close reading and textual analysis. The second half of the paper examines the novel from the perspective of the traditional formats and subversive recycling of life writing, body studies and female madness.